2017
DOI: 10.1016/j.jconhyd.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Field data and numerical simulation of btex concentration trends under water table fluctuations: Example of a jet fuel-contaminated site in Brazil

Abstract: Mass transfer of light non-aqueous phase liquids (LNAPLs) trapped in porous media is a complex phenomenon. Water table fluctuations have been identified as responsible for generating significant variations in the concentration of dissolved hydrocarbons. Based on field evidence, this work presents a conceptual model and a numerical solution for mass transfer from entrapped LNAPL to groundwater controlled by both LNAPL saturation and seasonal water table fluctuations within the LNAPL smear zone. The numerical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 69 publications
1
20
0
3
Order By: Relevance
“…In tropical and subtropical climates, the amplitude of the water table fluctuation is typically high [15,20]. Under these conditions, the LNAPL may be completely entrapped below the water table, as described by Isler et al [21].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…In tropical and subtropical climates, the amplitude of the water table fluctuation is typically high [15,20]. Under these conditions, the LNAPL may be completely entrapped below the water table, as described by Isler et al [21].…”
Section: Introductionmentioning
confidence: 95%
“…The concentration decline is related to several factors, such as the LNAPL saturation, flow velocity, and biodegradation rates in the aqueous phase. Teramoto and Chang [15], Mackay et al [23], Huntley and Beckett [24], and Thornton et al [25], among others, demonstrated that the continuous loss of water-soluble compounds leads to continuous depletion of LNAPL in the source zone. Actually, there are a large number of analytical and numerical approaches, varying in scale and complexity, to simulate NAPL dissolution into the aqueous phase [18,[26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Como demonstrado por Teramoto & Chang (2017), a solubilização da fase líquida não-aquosa (NAPL) em área contígua à do presente estudo é resultado de inúmeros fatores, tais como velocidade de fluxo, taxa de biodegradação, saturação da fase não aquosa e da flutuação do nível d'água. Entretanto, para simplificação do modelo, admitiu-se a existência de equilíbrio termodinâmico entre a água e o NAPL no poro, baseando-se na Lei de Raoult (BANERJEE, 1984), com a fixação de uma concentração na porção compreendida pela área-fonte idealizada.…”
Section: Cenário Hipotético De Contaminaçãounclassified